TANGGUNG JAWAB PEMILIK TEMPAT PENITIPAN ANAK TERHADAP TIDAK TERPENUHINYA STANDAR SARANA DAN PRASARANA MENURUT PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN NOMOR 137 TAHUN 2014 TENTANG STANDAR NASIONAL PENDIDIKAN ANAK USIA DINI (Studi Di Tempat Penitipan Anak Rumah Ananda Kota Pekanbaru) - Desi Nurliana; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The growing number of parents working outside the home makes the family function as a place to educate the child less. Often, parents submit parenting and children's education to other people (institutions or institutions) that grow a lot of mushrown, especially in large cities such as the daycare places of Ananda Kota Pekanbaru.This type of research is sociological, because in this research the author directly conducts research on the location or place studied to provide a complete and clear picture of the problem studiedBased on the results of the research problem there are two points that can be concluded, first, the existence of the legal relationship between the owner of the nursery with parents is the relationship in carrying out the child care Agreement. The owner of the nursery and the parents here as the owners of rights and obligations where the objective is the achievement of services that must be given the owner to the child who deposited and the child/parent as the subject/perpetrator of activities and owners as Facilitator so that the parents can say as a service user and the owner of a nursery as a service provider. Secondly, the owner of the nursery does not carry out its responsibilities in fulfilling the facilities and infrastructure as well as in the administration process. The facilities and infrastructures that have not been fulfilled are not yet maintain good hygiene and lack of standard feasibility. The nursery owners of the Ananda House also do not have a standard operational procedure (SOP), and do not make an annual report. Author's suggestion, first, is expected to the daycare owner to foster awareness about the importance of knowing and fulfilling the standard of worthiness for a daycare for safety and comfort for children who be stored at. Second, it is expected to the relevant service to further improve the supervision of daycare that stands in Pekanbaru city such as increasing the performance of the viewer to more actively supervise and foster a nursery that does not comply with Standards of eligibility and provide strict sanctions for daycare that does not improve its facilities and infrastructure.Keywords: Responsibility - The daycare - Pekanbaru